1973
DOI: 10.1055/s-0028-1099487
|View full text |Cite
|
Sign up to set email alerts
|

DITERPENCHINONE AUS LABIATENWURZELN1

Abstract: r i e s k o r n und L. B u c h b e r g e r [I] SummaryThe roots of Salvia officinalis, Salvia pratensis and Rosmarinus officinalis contain royleanon and/or derivatives of royleanon. Additional cryptotanshinon is found in Rosrnarintzs officinalis.Die innersten Rindenschichten der frischen Wurzeln von Salvia officinalis, S. pratensis und Rosmarinus officinalis zeigen eine gelbe bis orangegelbe Farbe. Beim Lagern der Wurzeln geht sie in ein schmutziges Braun iiber. Die farbigen Pigmente lassen sich den luflgetroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…They stated that the compounds were identical to those isolated by Brieskorn and Buchberger (1982) and Hensch et al (1975) but the structures they showed in their paper are missing the hydroxy group at C-12, mistakenly driving to the conclusion that they have indeed isolated both 1 and its -epimer. A patent filling, written in Japanese, for a novel diterpene quinone useful as an aldose reductase inhibitor was found in the literature (Koiwai et al, 1990).…”
Section: Resultsmentioning
confidence: 92%
“…They stated that the compounds were identical to those isolated by Brieskorn and Buchberger (1982) and Hensch et al (1975) but the structures they showed in their paper are missing the hydroxy group at C-12, mistakenly driving to the conclusion that they have indeed isolated both 1 and its -epimer. A patent filling, written in Japanese, for a novel diterpene quinone useful as an aldose reductase inhibitor was found in the literature (Koiwai et al, 1990).…”
Section: Resultsmentioning
confidence: 92%
“…Subsequently, the hydroxyl at C11 drives the entry of another hydroxyl substituent to C14 ( p -position). The oxidation of o -hydroxyhydroquinone leads to the formation of o -hydroxy- p -benzoquinone [ 32 ].…”
Section: Abietane Diterpenes Of the Genus Plectranthus Slmentioning
confidence: 99%
“…The main antioxidative effect of it was reported to relate to the presence of carnosic acid, carnosol, and rosmarinic acid . In addition, other diterpenes, triterpenes and flavonoids, have been isolated from sage. …”
Section: Introductionmentioning
confidence: 99%